Security gaps assessment of smart grid based SCADA systems. (17th June 2019) - Mir, Abdul Wahid; Ketti Ramachandran, Ramkumar
Abstract : Purpose: Supervisory control and data acquisition (SCADA) systems security is of paramount importance, and there should be a holistic approach to it, as any gap in the security will lead to critical national-level disaster. The purpose of this paper is to present the case study of security gaps assessment of SCADA systems of electricity utility company in the Sultanate of Oman against the regulatory standard and security baseline requirements published by the Authority for Electricity Regulation (AER), Government of Sultanate of Oman. Design/methodology/approach: The security gaps assessment presented in this paper are based on the security baseline requirements that include core areas, controls for each core area and requirements for each control. Findings: The paper provides the security gaps assessment summary of SCADA systems of electricity utility company. Practical implications: The summary of threats and vulnerabilities presented will help stakeholders to be proactive rather than reactive in the event of any attack. Originality/value: This case study discusses the various security challenges in smart grid based on SCADA systems and provides the summary of challenges and recommendations to overcome the same.